2021
DOI: 10.5194/nhess-21-21-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Brumadinho tailings dam failure, the subsequent loss of life and how it could have been reduced

Abstract: Abstract. In recent years the number of tailings dams failures has increased. On 25 January 2019, the Brumadinho tailings dam in Brazil suddenly failed, releasing a mudflow over 10 m deep comprising some 107 m3 of mining waste which killed between 270 and 320 people. This paper details the use of an agent-based model, known as the Life Safety Model (LSM), to estimate the risk to people downstream of the Brumadinho tailings dam and to assess if the number of fatalities could have been reduced if a warning had b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…Therefore, this model used the "do not bulk" function in HEC-RAS, while the HEC-RAS bulked the clear water hydrographs during the simulation in the Santa Barbara models, based on the C v . The volumetric concentration (28% solids) in Lumbroso et al's (2021) [20] study was lower than Robertson et al's (2019) [3], who reported that ~50% of impoundment was saturated voids and ~58% (7 of the total 12 million m 3 released) of the debris materials were solids. However, because this model used constant Bingham parameters (instead of Julien's (1995) concentration-dependent equations) and the hydrograph included the mud volume, the HEC-RAS simulation was not sensitive to the volumetric concentration selected.…”
Section: Brumadinho Model Model Parameters and Input Data: Brumadinhomentioning
confidence: 58%
See 2 more Smart Citations
“…Therefore, this model used the "do not bulk" function in HEC-RAS, while the HEC-RAS bulked the clear water hydrographs during the simulation in the Santa Barbara models, based on the C v . The volumetric concentration (28% solids) in Lumbroso et al's (2021) [20] study was lower than Robertson et al's (2019) [3], who reported that ~50% of impoundment was saturated voids and ~58% (7 of the total 12 million m 3 released) of the debris materials were solids. However, because this model used constant Bingham parameters (instead of Julien's (1995) concentration-dependent equations) and the hydrograph included the mud volume, the HEC-RAS simulation was not sensitive to the volumetric concentration selected.…”
Section: Brumadinho Model Model Parameters and Input Data: Brumadinhomentioning
confidence: 58%
“…Given the high void ratio, Robertson et al (2019) [3] estimated that 5 million m 3 of the total 12 million m 3 impoundment was water. Lumbroso et al (2021) [20] developed a mixed-material breach hydrograph with Roberson et al's (2019) [3] volume estimates and two-fluid EMBREA-MUD simulations (Figure 1b). They estimated that the event reached a peak mudflow rate of 90,000 cms within 5 s of the failure and gave the mixed-material hydrograph a "stepped" structure based on video evidence of progressive failure and mudflow velocities.…”
Section: Brumadinho Mine Tailings Dam Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The 86 m height tailings dam, constructed with the upstream method, catastrophically failed, releasing 12 million m 3 of mineral waste. Catastrophic failures at Samarco and Brumadinho in 2015 and 2019, respectively, brought mine tailings disasters onto the global level in unprecedented ways, and several studies have developed these themes following these events (e.g., [6,[11][12][13][14][15][16]).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [31] designed a cell-based network model to gain deep insights into staged evacuation features. Many evacuation studies, however, have focused solely on either hard infrastructure or institutional arrangements though there are some models, such as the Life Safety Model (LSM), which incorporate both sides (please refer to Refs [24][25][26][36][37][38][39]). Addressing the interplay between efficiency and fairness in urban flood evacuation requires an approach that integrates both the hard infrastructural and institutional aspects of the problem.…”
Section: Introductionmentioning
confidence: 99%